Development of Theological Concept of Mission in Scripture - Evgeny FURSOV (Богословські роздуми: Східноєвропейський журнал богословʼя)
The traditional understanding of mission is based on the Great Commission in Matt. 28:19-20. As a result mission is often considered as feature of the New Testament period which to some degree restrains its understanding. This article explores development of the concept of mission in Scripture with the purpose of defining in which way both Old and New Testaments represent the wholeness of the concept of mission. In the first part of the article the author considers God's covenants with Noah, Abraham, and also the Sinaic covenant, emphasizing the missional nature of the covenants. From a theological perspective the Old Testament points to the redemptive character of mission. In the second part the author explores God's missional relation to the world and also raises the question of the Church's missional relation to the world. Thus the Church's mission is not only about following the Great Commission’s “to go”, but also about “being”. Within this framework the mission of the Church can obtain different forms, meeting physical, emotional and spiritual needs of people.